departments and effects of legal controls for tax checking up in Iraq - Safa Abdul-Mahdi Jasim, Researcher; Mohammad Bidar , Dr. (lark, 2023)
It is legally known that the Tax Law must correspond with the economic, social, and cultural foundations of society. Although most countries in the world adopt several and complex tax systems, the procedures and regulations for tax examination in Iraq are still in need of new tax legislation that guarantees legitimacy Tax checking up and its effects. Since the topic of the study is the procedures and effects of legal regulations for tax checking up in Iraq, the problem of the study is represented in the main question, which is what are the legal regulations for tax checking up in Iraq? By using the contrastive descriptive and analytical research method, it is found that the original hypothesis of the study is true, which is that the legal regulations for tax examination are carried out through what the Tax authority (tax administrations or the General Commission for Taxes) does in Iraq is to check the files of the financiers periodically. That ensures the extent of the credibility of the tax return submitted by the financier to the Tax Authority with his profits and expenses. Tax Authority carries out the checkup process through its different directorates at the level of Iraq. This is considered as the tax procedures which are carried out by the different directorates. Also, the collection of these taxes will have effects reflected on society and the state negatively or positively. The study reaches a set of results and recommendations. The most important of which is that the general legal regulations for tax checking up in Iraq are based on a set of standards namely the basic rules that the legislator should take into consideration when imposing taxes. Its importance stems from the necessity to compatible between the interests of the taxpayer and the state alike. Therefore, the criteria of distinguishing between direct and indirect taxes in Iraq are not sufficient. The study recommends the need for a comprehensive and unified law and not several laws to impose taxes. In light of the existence of the independent institution that applies the law to impose taxes in Iraq, which is called Tax Institution or General Tax Authority that is governed by Unified Tax Law in Iraq. It includes a set of rules and controls that regulate the relationship of the state with the individual in the field of taxation. It takes several forms that may be in the form of the Income Tax Law, or in the form of the Customs Tax Law, all of which are issued by the legislative authority. This will improve the tax reality and make the tax administration more control when its laws are stable.
Keywords: Legal Controls - Tax Checking up - Iraqi Law.